2007
DOI: 10.1007/s00209-007-0171-y
|View full text |Cite
|
Sign up to set email alerts
|

$${\mathbb{Z}}_2^k$$ -Manifolds are isospectral on forms

Abstract: We obtain a simple formula for the multiplicity of eigenvalues of the HodgeLaplace operator, f , acting on sections of the full exterior bundle * (TM) = n p=0 p (TM)over an arbitrary compact flat Riemannian n-manifold M with holonomy group Z k 2 , 1 ≤ k ≤ n − 1. This formula implies that any two such manifolds having isospectral lattices of translations are isospectral with respect to f . As a consequence, we construct a large family of pairwise f -isospectral and nonhomeomorphic n-manifolds of cardinality gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…with B 2 i = Id, then we can assume that b j · e i = 0 or 1 2 for every 1 ≤ i ≤ n, 1 ≤ j ≤ k. Although this definition clearly imposes a restriction on Γ , this is still a very rich class of Bieberbach groups (see for instance [9]). …”
Section: Diagonal Bieberbach Groupsmentioning
confidence: 98%
See 3 more Smart Citations
“…with B 2 i = Id, then we can assume that b j · e i = 0 or 1 2 for every 1 ≤ i ≤ n, 1 ≤ j ≤ k. Although this definition clearly imposes a restriction on Γ , this is still a very rich class of Bieberbach groups (see for instance [9]). …”
Section: Diagonal Bieberbach Groupsmentioning
confidence: 98%
“…Note that a GHW group is of type HW if and only if it is orientable. We refer to [3,9,24] for more facts on these groups. For instance, in [9] it is shown that all GHW manifolds are isospectral on forms; that is, for the full Hodge-Laplacian acting on p-forms for all 0 ≤ p ≤ n. This also holds for the family K n .…”
Section: The Family K Nmentioning
confidence: 99%
See 2 more Smart Citations